The modulatory role of cytokines IL-4 and IL-17 in the functional activity of phagocytes in diabetic pregnant women - Fagundes, Danny L. G. [UNESP]; França, Eduardo L.; Gonzatti, Michelangelo B.; Rugde, Marilza V. C. [UNESP]; Calderon, Iracema M. P. [UNESP]; Honorio-França, Adenilda C. (Wiley, 2018)
The study investigated the role of cytokines IL-4 and IL-17 in the modulation of the functional activity of mononuclear phagocytes in diabetic pregnant women with hyperglycemia. Sixty pregnant women were assigned to the following groups: nondiabetic (ND), mild gestational hyperglycemia (MGH), gestational diabetes mellitus (GDM), or type 2 diabetes mellitus (DM2). The functional activity of phagocytes from maternal blood, cord blood, and colostrum was assessed by determining their superoxide release, phagocytosis, microbicidal activity, and intracellular Ca2+ release. Irrespective of glycemic status, colostrum and blood cells treated with IL-4 and IL-17 increased superoxide release in the presence of enteropathogenic Escherichia coli (EPEC). The highest phagocytosis rate was observed in cells from the DM2 group treated with IL-4. In all the groups, phagocytes from colostrum, maternal blood, and cord blood exhibited higher microbicidal activity against EPEC when treated with cytokines. IL-17 increased intracellular Ca2+ release by colostrum phagocytes in diabetic groups. The results indicate that the IL-4 and IL-17 modulate the functional activity of phagocytes in the maternal blood, cord blood, and colostrum of diabetic mother. The natural immunity resulting from the interaction between the cells and cytokines tested may be an alternative procedure to improve the prognosis of maternal and newborn infections.
Keywords: cytokines; Diabetes; mild gestational hyperglycemia; phagocytes